Need for Speed: The Importance of Physiological Strain Rates in Determining Myocardial Stiffness - Caporizzo, Matthew A.; Prosser, Benjamin L. (Frontiers in Physiology, 2021)
The heart is viscoelastic, meaning its compliance is inversely proportional to the speed at which it stretches. During diastolic filling, the left ventricle rapidly expands at rates where viscoelastic forces impact ventricular compliance. In heart disease, myocardial viscoelasticity is often increased and can directly impede diastolic filling to reduce cardiac output. Thus, treatments that reduce myocardial viscoelasticity may provide benefit in heart failure, particularly for patients with diastolic heart failure. Yet, many experimental techniques either cannot or do not characterize myocardial viscoelasticity, and our understanding of the molecular regulators of viscoelasticity and its impact on cardiac performance is lacking. Much of this may stem from a reliance on techniques that either do not interrogate viscoelasticity (i.e. use non-physiological rates of strain) or techniques that compromise elements that contribute to viscoelasticity (i.e. skinned or permeabilized muscle preparations that compromise cytoskeletal integrity). Clinically, cardiac viscoelastic characterization is challenging, requiring the addition of strain-rate modulation during invasive hemodynamics. Despite these challenges, data continues to emerge demonstrating a meaningful contribution of viscoelasticity to cardiac physiology and pathology, and thus innovative approaches to characterize viscoelasticity stand to illuminate fundamental properties of myocardial mechanics and facilitate the development of novel therapeutic strategies.